If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -7) = 4(3 + x) Reorder the terms: 3(-7 + 2x) = 4(3 + x) (-7 * 3 + 2x * 3) = 4(3 + x) (-21 + 6x) = 4(3 + x) -21 + 6x = (3 * 4 + x * 4) -21 + 6x = (12 + 4x) Solving -21 + 6x = 12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -21 + 6x + -4x = 12 + 4x + -4x Combine like terms: 6x + -4x = 2x -21 + 2x = 12 + 4x + -4x Combine like terms: 4x + -4x = 0 -21 + 2x = 12 + 0 -21 + 2x = 12 Add '21' to each side of the equation. -21 + 21 + 2x = 12 + 21 Combine like terms: -21 + 21 = 0 0 + 2x = 12 + 21 2x = 12 + 21 Combine like terms: 12 + 21 = 33 2x = 33 Divide each side by '2'. x = 16.5 Simplifying x = 16.5
| 14x^4+14x^3-x^2-x=0 | | -4x-19=-99 | | 6x-21=12+4x | | 5z-2z=3z-9+8z | | (((1.5b*b))/(1.5b*b))=50 | | 4z/(-16)=-6 | | -1-5s+6s=5 | | (1.5b*b)=50 | | 4p*2q=30 | | 55r^2-14r-23=0 | | 11+4x=7(x-1) | | 5z-9z=-7z-7-z | | 40=x(x+3) | | 2x+x/2+x+20=580 | | (5w+1)(2-w)=0 | | (1.5*b)*b=0 | | 1.5b*b=0 | | X*2=-9x-8 | | 3x-5-2x=5-12 | | 0.5(4x-2)= | | (5x-90)=2x+30 | | C-6c=0 | | (11r+6)(5r-4)=0 | | Y=0.6(100)+b | | 6n^2/2 | | x+13=5x | | 5(x)=5(2x-3) | | R=b^2+1 | | (5x)2=15x-45 | | 3c-1=c | | 3x-5-x=2x-3 | | 3ysquared= |